Cis-Golgi cisternal assembly and biosynthetic activation occur sequentially in plants and algae - Donohoe, Bryon; Kang, Byung-Ho; Gerl, Mathias; Gergely, Zachary R.; McMichael, Colleen M.; Bednarek, Sebastian Y.; Staehelin, L. Andrew (Traffic, 2013)
The cisternal progression/maturation model of Golgi trafficking predicts that cis-Golgi cisternae are formed de novo on the cis-side of the Golgi. Here we describe structural and functional intermediates of the cis cisterna assembly process in high-pressure frozen algae (Scherffelia dubia, Chlamydomonas reinhardtii) and plants (Arabidopsis thaliana, Dionaea muscipula; Venus Flytrap) as determined by electron microscopy, electron tomography and immuno-electron microscopy techniques. Our findings are as follows: () The cis-most (C1) Golgi cisternae are generated de novo from cisterna initiators produced by the fusion of 3-5 COPII vesicles in contact with a C2 cis cisterna. () COPII vesicles fuel the growth of the initiators, which then merge into a coherent C1 cisterna. () When a C1 cisterna nucleates its first cisterna initiator it becomes a C2 cisterna. () C2-Cn cis cisternae grow through COPII vesicle fusion. () ER-resident proteins are recycled from cis cisternae to the ER via COPIa-type vesicles. () In S. dubia the C2 cisternae are capable of mediating the self-assembly of scale protein complexes. () In plants, ~90% of native α-mannosidase I localizes to medial Golgi cisternae. () Biochemical activation of cis cisternae appears to coincide with their conversion to medial cisternae via recycling of medial cisterna enzymes. We propose how the different cis cisterna assembly intermediates of plants and algae may actually be related to those present in the ERGIC and in the pre-cis Golgi cisterna layer in mammalian cells.